Optimization procedure for parameter determination of caboche kinematic hardening model. Issue 1 (July 2020) - Moslemi, Navid; Golzardian, Mohsen; Redzuan, Norizah; Mozafari, Farzin; Ayob, Amran
Abstract: The ratcheting behavior and prediction of 316L stainless steel pipe was developed using numerical finite elementapproach. The Chaboche model parameters to be used in the numerical method were adopted from symmetric post monotonic teston the pipe. The significant property, the elastic limitof the material, was extracted using incremental cyclic uniaxial test. Comparison between two well-known optimization methods, Particle Swarm Optimization and Genetic Algorithm gave the former a slightly better correlation with experimental tests.The Chaboche model in ANSYS was utilized to predict the uniaxial ratcheting behavior of the pipe specimen. Theclose comparison of rate of ratcheting between finite element simulation and experimental test indicates that accurate elastic limit extraction from post monotonic test alone results in improved ratcheting prediction, with PSO method adopted to optimize ratcheting parameters.